Textile Industry and Environment - Körlü, Ayşegül (IntechOpen, 2019)
In this book, the relationship between the textile industry and the environment is examined from four different viewpoints. Recycling of spinning mill wastes, ozone usage that provides less chemical and water utilization, reuse of treated water in the dyeing processes, and approaches in the treatment of wastewaters of dyeing plants and finishing factories are solutions offered to reduce environmental pollution arising from textile production processes. Apart from this, energy management is also a subject that can be associated with the environment, and as a consequence, the possibility of utilizing textile materials to which phase change materials are applied, not only for comfort purposes but also as energy storage materials, means that technical textiles could be a solution for energy storage.